Flood Inundation Analysis for Huay Sompoy Sub-basin in Kaisone Phomvihane City Savannakhet Province - PHONNASANE, Vanhthone; KIMMANY, Bounhome; SITHAVONG, Saykham (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
Flooding is one of the most significant natural hazards affecting socio-economic development, environmental sustainability, and public safety in the Lao People's Democratic Republic. The Huay Sompoy Sub-basin, located in Kaisone Phomvihane City, Savannakhet Province, experiences frequent flooding due to prolonged rainfall, low-lying topography, and increasing hydrological variability. This study aimed to analyze flood inundation areas and develop flood hazard maps for the Huay Sompoy Sub-basin by integrating the Hydrologic Engineering Center–River Analysis System (HEC-RAS) with Geographic Information Systems (GIS). The hydraulic model was developed using Digital Elevation Model (DEM) data, land-use information, soil characteristics, river cross-sections, and simulated discharge data generated from the HEC-HMS model. Rainfall and hydrological records collected between 2010, 2019 and 2024 were used for model calibration and validation to ensure simulation reliability. The validated HEC-RAS model was employed to simulate flood inundation events for representative flood years and generate spatial flood hazard maps using ArcGIS. The results demonstrate that the hydraulic model accurately reproduced flood characteristics and successfully identified inundation extent, flood depth, and vulnerable areas within the watershed. In 2019 was very high effect from flood as measure about 14.50 meter and cover about 2,776.25 ha. The flood maps reveal that low-lying agricultural land, residential communities, and areas adjacent to the main river channels are highly susceptible to flooding during high-flow events. The integration of HEC-RAS and GIS proved to be an effective approach for visualizing flood-prone areas and supporting flood risk assessment. The findings provide valuable scientific information for disaster risk reduction, land-use planning, infrastructure development, and sustainable watershed management in the Huay Sompoy Sub-basin. Furthermore, the study offers a practical framework for improving flood preparedness and strengthening climate change adaptation strategies in Savannakhet Province and other flood-prone watersheds in the Lao PDR.